VD_FINDINFO Jug / 2013 / 125 vom 20. November 2012 - VD Tribunal cantonal (2012)
VIOLENCE CONTRE LES AUTORITÉS, FIXATION DE LA PEINE, PEINE PÉCUNIAIRE, REVENU DÉTERMINANT | 285 ch. 1 CP, 34 al. 2 CP, 47 CP